Volatile Organic Compounds in Human Exhaled Breath to Diagnose Gastrointestinal Cancer: A Meta-Analysis - Xiang, Lijuan; Wu, Sihan; Hua, Qingling; Bao, Chuyang; Liu, Hu (Frontiers in Oncology, 2021)
Introduction: Human exhaled volatile organic compounds(VOCs) are being extensively studied for the purposes of noninvasive cancer diagnoses. This article was primarily to assess the feasibility of utilizing exhaled VOCs analysis for gastrointestinal cancer(GIC) diagnosis. Methods: PRISMA-based system searches were conducted for related studies of exhaled VOCs in GIC diagnosis based on predetermined criteria. Relevant articles on colorectal cancer and gastroesophageal cancer were summarized, and meta analysis was performed on articles providing sensitivity and specificity data. Results: From 2227 articles, 14 were found to meet inclusion criteria, 6 of which were on colorectal cancer(CRC) and 8 on Gastroesophageal cancer(GEC). 5 articles could provide specific data of sensitivity and specificity in GEC, which were used for meta-analysis. The pooled sensitivity, specificity, diagnostic odds ratio(DOR), and area under the curve(AUC) were calculated based on the combination of these data, and were 85.0%(95% confidence interval(CI): 79.0%-90.0%), 89.0% (95%CI: 86.0%-91.0%), 41.30(21.56-79.10) and 0.93, respectively. Conclusion: Exhaled VOCs are promising tumor biomarkers for GIC diagnosis .